PENGARUH JARAK TANAM DAN KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L. Merill) - Kalasari, Rastuti; Aminah, R. Iin Siti; Palmasari, Berliana; Aprike, Yongki (Universitas Muhammadiyah Palembang, 2021)
Effect of planting distance and concentration of liquid organic fertilizer on growth and production of soybean (Glycine max L. Merill). This study aims to determine and obtain the best spacing with liquid organic fertilizer concentration on the growth and production of soybean (Glycine max L. Merill). This research has been carried out on the land of Tanjung Raja village, North Musi Rawas Regency, South Sumatra Province. This research was conducted from May to August 2019. This study used a split-plot design field experiment. With 12 treatment combinations and repeated 3 times. The treatment factors are as follows: Plant Planting Distance (J) consists of: J1: 20 cm x 20 cm, J2: 40 cm x 20 cm, J3: 60 cm x 20 cm, The dose of Liquid Organic Fertilizer (O) consists of: O0 : Control (without poc), O1 : 20 ml/liter, O2 : 30 ml/liter, O3: 40 ml/liter. The variables observed in this study were plant height (cm), number of primary branches (stalk), number of pods planted, number of cipo pods (empty), yield per clump (g), weight of 100 seeds (g). Based on the results of the study, it was stated that the treatment with a spacing of 20 cm x 20 cm with a concentration of liquid organic fertilizer 40 ml/liter of water gave the highest yield of 49.13 plants or 9.83 tons/ha.